Perbandingan Kode Etik Hakim Konstitusi Antara Indonesia Dan Jerman - Wahyuda, Muhammad Riyan; Kartika, Adhitya Widya (Universitas Widya Gama Malang, 2025)
The research studied by the author aims to understand and compare the regulation of the code of ethics of Indonesian and German constitutional judges and explain the regulation of the code of ethics of German judges stipulated in the BDG. The author conducts this research in a normative manner that analyzes norms in legislation using a comparative approach and statute approach. Indonesia and Germany have similar legal systems and similar historical backgrounds where both countries have experienced authoritarian regimes, so the Constitutional Court is present to prevent this from reappearing. The results showed that the Constitutional Court Regulation related to the code of ethics for constitutional judges refers to The Bangalore Principles 2002. The Constitutional Court Regulation itself has the same position as the Presidential Regulation